Microstrip patch antenna with metamaterial using superstrate technique for wireless communication - Rasha Mahdi Salih; Ali Khalid Jassim (Institute of Advanced Engineering and Science, 2021)
This work builds a metamaterial (MTM) superstrate loaded on a patch of microstrip antenna for wireless communications. The MTM superstrate is made up of four G-shaped resonators on FR-4 substrate with a relative permittivity of 4.4 and has a total area of (8×16) mm2, and is higher than the patch. The MTM superstrate increases antenna gain while also raising the input reflection coefficient. When it is 9 mm above the patch, the gain increased from 3.28 dB to 6.02 dB, and when it is 7 mm above the patch, the input reflection coefficient was enhanced from -31.217 dB to -45.8 dB. When the MTM superstrate loaded antenna was compared to the traditional unloaded antenna, it was discovered that metamaterials have a lot of potential for improving antenna performance.